Accelerated approval drug labels often lack information for clinical decision‐making. Issue 4 (16th March 2023) - Ballreich, Jeromie; Socal, Mariana; Bennett, Charles L.; Xuan, Andrew; Trujillo, Antonio; Anderson, Gerard
Abstract: Study objective: We evaluated US Food and Drug Administration labels for drugs approved under the accelerated approval pathway and whether these labels contained in sufficient information regarding their accelerated approval. Design: Retrospective, observational, cohort study. Data source: Label information for drugs with an accelerated approved indication were ascertained from two online platforms: Drugs@FDA and FDA Drug Label Repository. Intervention: Drugs with indications receiving accelerated approval after January 1, 1992, but had not received full approval by December 31, 2020. Measurements: Outcomes include whether the drug label indicated the use of the accelerated approval pathway, identified the specific surrogate marker(s) that supported it, or described the clinical outcomes being evaluated in post‐approval commitment trials. Results: 253 clinical indications corresponding to 146 drugs received accelerated approval. We identified a total of 110 accelerated approval indications across 62 drugs that had not received full approval by December 31, 2020. A total of 13% of labels for accelerated approved indications lacked sufficient information that approval was via the accelerated approval or based on surrogate outcome measures: 7% did not mention accelerated approval but described surrogate markers, 4% did not mention accelerated approval nor describe surrogate markers, and 2% mentioned accelerated approval but did not describe surrogate markers. No label described the clinical outcomes being evaluated in post‐approval commitment trials. Conclusion: Labels for accelerated approved clinical indications that do not yet have full approval should be revised to include the information required in the FDA guidance to help guide clinical decision‐making.